Morphological changes in white blood cells in systemic inflammatory response syndrome (SIRS) with and without sepsis: An observational study - Siddharth Sharma; Kumari Pratima; Shivlok Narayan Ambedkar; Rajesh Kumar; Meghraj Kundan (Journal of Family Medicine and Primary Care)
Background: This is an observational study which aims to research morphological changes of white blood cells in patients with Systemic Inflammatory Response Syndrome (SIRS) with and without sepsis and evaluate morphological changes in white blood cells as predictors of sepsis. Methods: Patients aged 18 years or more with SIRS with sepsis and SIRS without sepsis were included and those with haematological disorders or pregnant patients were excluded. A total of 52 patients with SIRS with sepsis and 32 patients of SIRS without sepsis were included. Peripheral blood smear was prepared from the venous blood sample drawn. The presence of toxic granules, cytoplasmic vacuoles, and Dohle bodies in both cases of SIRS with sepsis without sepsis were assessed and it was compared with culture-positive sepsis and shock. Results: The difference in the presence of toxic granules (55.8% vs. 12.5%; p <0.001), cytoplasmic vacuoles (30.8% vs. 6.3%; p -0.012), and Dohle bodies (17.3% vs. 0%; p = 0.012) was significantly higher in the SIRS with sepsis group, compared to the SIRS without sepsis group. In the subgroup analysis of patients in the sepsis group, it was observed that patients with positive blood culture (9%) had a significantly higher proportion of toxic granules (100% vs. 51.1%; p=0.059), cytoplasmic vacuoles (40% vs. 29.8%; p=0.637) and Dohle bodies (40% vs. 14.9%; p=0.202). However, these differences were not statistically significant. Conclusion: Toxic granules and cytoplasmic vacuoles in the neutrophils of patients with SIRS with sepsis were found more frequently, compared to patients of SIRS without sepsis. Dohle bodies were found only in patients with sepsis and not in those with SIRS without sepsis.